2020
DOI: 10.3389/fcell.2020.00020
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence and Mutual Exclusivity Analysis of DNA Methylation Reveals Distinct Subtypes in Multiple Cancers

Abstract: Co-occurrence and mutual exclusivity (COME) of DNA methylation refer to two or more genes that tend to be positively or negatively correlated in DNA methylation among different samples. Although COME of gene mutations in pan-cancer have been well explored, little is known about the COME of DNA methylation in pan-cancer. Here, we systematically explored the COME of DNA methylation profile in diverse human cancer. A total of 5,128,332 COME events were identified in 14 main cancers types in The Cancer Genome Atla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Previous studies have revealed mutually exclusive patterns of genomic alterations across cancer patients, including mutations in driver genes [ 26 ]. Genes exhibiting mutually exclusive alternation pattern are generally involved in a common biological pathway due to their functional redundancy [ 27 , 28 ]. Knowledge about these patterns can provide important insight into novel cancerous network and potential therapeutic targets [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have revealed mutually exclusive patterns of genomic alterations across cancer patients, including mutations in driver genes [ 26 ]. Genes exhibiting mutually exclusive alternation pattern are generally involved in a common biological pathway due to their functional redundancy [ 27 , 28 ]. Knowledge about these patterns can provide important insight into novel cancerous network and potential therapeutic targets [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…DNMIVD ( http://www.unimd.org/dnmivd/ ) is a database that allows researchers to build molecular models for diagnosis and prognosis of cancer based on methylation of DNA, and visualizes the methylation profile of gene promoters and CpGs from various aspects [ 52 54 ]. We analyzed the expression level and methylation value of CDH23 in breast invasive carcinoma (BRCA) and normal tissues, and further calculated the Pearson correlation between methylation of CDH23 promoter and Fragments Per Kilobase of exon model per Million mapped fragments (FPKM) in BRCA.…”
Section: Methodsmentioning
confidence: 99%
“…The methylation difference of STEAP1 between normal and tumor samples was evaluated. DNA methylation interactive visualization database (DNMIVD, http://119.3.41.228/ dnmivd/index/) was used to investigate the methylation of STEAP1 regarding the correlation between STEAP1 expression level in Fragments Per Kilobase Million (FPKM) form and the methylation level of its promoter [19][20][21]. The mutation exploration was carried out by cBioPortal (https://www.cbioportal.org/), an open-access resource for interactive analysis of all-round cancer genomics datasets.…”
Section: Biological Analysis and Tumor Microenvironment (Tme)mentioning
confidence: 99%